Effectiveness of WHO Stress Management for Improving Insomnia Severity Index Score in Telegram’s Self-Isolated Online Group Population - Ines Damayanti Octaviani; Gusti Ayu Maharatih; Adriesti Herdaetha (Majalah Kedokteran Bandung, 2023)
Insomnia is one of the various symptoms frequently found in patients with post-covid syndrome (PCS) (19.1%). The WHO Stress Management (WSM) is an eclectic psychotherapy that combines mindfulness and relaxation which, theoretically, can be effective in treating insomnia due to PCS. This study aimed to explore the effectiveness of WSM in improving the Insomnia Severity Index Score for people with PCS. This was a quasi-experimental pre-test-post-test control study on 18 participants in the population of online self-isolation group in the Telegram who experienced insomnia. The intervention applied was WSM. These participants were compared to 18 controls who only received psychoeducation. Clinical insomnia symptoms were examined using the Insomnia Severity Index (ISI) before the intervention, then the control group was given sleep hygiene psychoeducation, and the treatment group was given WSM in 5 Zoom on-cam meetings once a week for 30-60 minutes. A re-assessment using the ISI post-test was then performed, and data were analyzed statistically. There was a change in score for insomnia symptoms in the treatment group (delta score 27.50) compared to the control group (delta score 9.50, p=0.00; OR 0.00, p=0,99, 95% CI). Thus, WSM can improve the insomnia score in the population with PCS.